A comparative study of biochemical parameters in mild and severe cases of COVID-19 - Gulavani, Gouri A.; Wali, Smita V.; Panchbudhe, Sanjyoti A. (International Journal of Research in Medical Sciences, 2021)
Background: COVID-19 has a range of clinical manifestations, including cough, fever, breathlessness, diarrhoea. Diagnosis of COVID-19 is commonly made through detection of SARS-CoV-2 RNA by PCR testing of a nasopharyngeal swab or other specimens. Evaluation and management of COVID-19 depend on the severity of the disease. This study was done to analyses the difference in the laboratory findings of the mild and severe cases in patients with COVID-19. Methods: In this study biochemical parameters of the patients with mild and those admitted in intensive care unit (ICU) of SKNMCGH, Pune were studied. Total 60 patients were included in this study. Standard deviation and mean were calculated from the values of biochemical parameters of COVID-19 patients in intensive care unit (ICU) and ward patients. Conclusions: We found levels of lactate dehydrogenase (LDH), C-reactive protein (CRP), Aspartate aminotransferase (AST), alanine aminotransferase (ALT), ferritin were significantly elevated in severely ill ICU admitted patients than mild patients. This may be useful for predicting progression towards a more severe form of COVID-19.